The Influence of Leadership and Work Motivation on the Performance of Employees at Selabintana Chicken Farm Garut - Sarip Hidayatulloh; Andri Muhammad Nuroni; Asep Saepuloh; Abdul Fatah Hassanudin (Outline Journal of Community Development, 2024)
Using the associative descriptive method, this is done to convey how the results of the research are conducted. The population in this review is 65 employees. The sample is part of the totality and characteristics of the population. The research analysis conducted by the author uses the multiple linear regression method, which is in accordance with the phenomenon of the research problem. Multiple linear regression is also an analysis used to determine the cause and effect of the variables studied. Overall leadership gets a Good assessment criterion, this criterion is indicated by the highest criterion, namely Leadership as a Motivator because leaders always provide a form of attention to their employees by providing complete direction and explanation in the work so that employees feel optimistic while working so that it causes employee performance to increase. Overall Work Motivation gets a Good criterion, this criterion is indicated by the highest criterion, namely the Need for Power because leaders provide a form of concern and attention given by the company in the form of promotion and determination of permanent employees has succeeded in making employee enthusiasm continue to increase while working so that it causes employee work motivation to increase. Overall Employee Performance gets Good criteria, this criteria is indicated by the highest criteria, namely Initiative because employees can solve their problems when working by using creative ideas and innovation in working so that effective and efficient working methods are obtained which have an impact on good product quality that can be produced through this working method, then overall employee performance gets good assessment criteria by being able to provide motivation from employees so that company goals are achieved.